Sistem Presensi dan Pengelolaan Tunjangan Kinerja Pegawai Resort Berbasis Web - Yofita Mulyaningsih; Olivia Kembuan; Sondy Kumajas (Program Studi Teknik Informatika, 2026)
Presence system and management of resort employee performance allowances using the web-based extreme programming method is system that is simplify the presence system and management of Resort employee performance benefits in Bogani Nani Wartabone National Park so that it can be accessed at anytime and at anywhere by Resort employees. This research was conducted on resort employees where the distance between each resort is quite far apart so a presence system is needed that can control each resort employee and can facilitate the calculation of performance allowances for each resort employee. The creation of this system uses the CodeIgniter framework for coding and a Database Management System (MySQL) for data management, resulting in a attendance system and management of resort employee performance allowances. Tthe conclusion is that based on the results of testing this system using black box testing and usability testing which was carried out on the Head of the National Park Management Section and Resort employees by distributing questionnaires, the average percentage score for system functionality elements was 91% and system satisfaction elements were 94%, while the final score for both this element is 92.5%, it can be concluded that it functions according to the expected goals.